An electrode sheet, a manufacturing method, a secondary battery, and a device
Patent Information
- Application Number
- CN202311229704.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-09-21
AI Technical Summary
[0003]发明目的:本申请的目的之一是提供一种极片,以解决单一粘结剂纤维化后的极片性能不佳的问题
[0038]Beneficial Effects: Compared with the prior art, the electrode of this application includes a current collector and an active material layer disposed on the current collector. The active material layer includes conductive polymer fibers, the mass percentage of which is y wt%. The aspect ratio of the conductive polymer fibers is R, the conductivity is C ms/cm, and the tensile strength is σ MPa, satisfying: 0.5 < lg[(y × σ × R)/C] < 5.0. By adding conductive polymer fibers to the active material layer, this application can form a dense fiber network inside the electrode, increasing the degree of fiberization and providing good conductivity for the active material layer. This reduces the tortuosity and resistance of the electrode, which is more conducive to lithium-ion transport and electrolyte wetting, effectively improving the dynamic performance of the secondary battery.
Smart Images

Figure BDA0004465271540000181 
Figure BDA0004465271540000191 
Figure BDA0004465271540000192
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary battery technology, specifically to an electrode, a preparation method, a secondary battery, and an apparatus. Background Technology
[0002] Battery electrodes prepared by connecting active materials and conductive agents using fibrous binders have advantages such as high compaction density and high thickness, which can significantly improve the kinetic performance of secondary batteries. However, due to the small particle size and large specific surface area of the binder, its degree of fibrosis is low; moreover, the binder is unevenly dispersed in the mixed system, making it difficult to control the degree of fibrosis. This directly results in low compaction density and high tortuosity of the electrode, thus affecting the performance of the secondary battery. Summary of the Invention
[0003] Purpose of the invention: One of the purposes of this application is to provide an electrode sheet that solves the problem of poor performance of electrodes after fiberization with a single binder.
[0004] Another objective of this application is to provide a method for preparing an electrode sheet; this application also provides a secondary battery; this application also provides an apparatus.
[0005] Technical Solution: An electrode sheet according to this application includes a current collector and an active material layer disposed on the current collector. The active material layer includes conductive polymer fibers, the mass percentage of which is y wt%. The aspect ratio of the conductive polymer fibers is R, the conductivity of which is Cms / cm, and the tensile strength of which is σMPa, satisfying the following conditions:
[0006] 0.5<lg[(y×σ×R) / C]<5.0.
[0007] In some embodiments, the active material layer further includes an active material and a binder, wherein the binder comprises b wt% by mass in the active material layer; and the specific surface area of the active material is 5 g / cm³. 2 The compaction density of the electrode sheet is PD g / cm³. 3 The tortuosity of the electrode is T, satisfying:
[0008] 1.4≤(S×T×b) / (PD×y)≤9.
[0009] In some embodiments, the electrode satisfies at least one of the following characteristics:
[0010] 1) The conductive polymer fiber is selected from at least one of conductive polyvinylidene fluoride fiber, conductive polytetrafluoroethylene fiber, conductive polyacrylonitrile fiber, conductive nylon fiber, conductive polyester fiber and conductive polyetheretherketone fiber;
[0011] 2) The aspect ratio R of the conductive polymer fiber satisfies: 200≤R≤1000;
[0012] 3) The conductivity C ms / cm of the conductive polymer fiber satisfies: 1≤C≤30000;
[0013] 4) The tensile strength σ MPa of the conductive polymer fiber satisfies: 1 ≤ σ ≤ 100;
[0014] 5) The diameter of the conductive polymer fiber is 0.01–1 μm;
[0015] 6) The length of the conductive polymer fiber is 10–1000 μm;
[0016] 7) The mass percentage of the conductive polymer fiber is y wt% and satisfies: 0.05≤y≤1.65.
[0017] In some embodiments, the electrode satisfies at least one of the following characteristics:
[0018] 1) The specific surface area S of the active material is 5 g / cm³ 2 It satisfies: 0.3 ≤ S ≤ 1.5;
[0019] 2) The mass percentage b wt% of the adhesive satisfies: 0.5 ≤ b ≤ 5;
[0020] 3) The active material in the active material layer has a mass percentage of 90-98 wt%;
[0021] 4) The conductive polymer fiber accounts for 0.1 to 33 wt% of the total amount of the adhesive;
[0022] 5) The compaction density PD of the electrode sheet (g / cm³) 3 Satisfies: 3.2≤PD≤4;
[0023] 6) The tortuosity T of the electrode sheet satisfies: 1.5≤T≤3.
[0024] In some embodiments, the electrode is a positive electrode, and the active material is a positive electrode active material selected from LiNi as shown in the formula. m Co n A (1-m-n) The lithium transition metal oxide represented by O2, wherein A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium and tungsten, and 0.5≤m≤1, 0≤n≤0.5.
[0025] In some embodiments, the electrode satisfies at least one of the following characteristics:
[0026] 1) The adhesive is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, polyethylene glycol, carboxymethyl cellulose and polyacrylate;
[0027] 2) The active material layer further includes a conductive agent, wherein the conductive agent has a mass percentage content of 0.5 to 5 wt% in the active material layer; the conductive agent is selected from at least one of conductive carbon black, Ketjen black, carbon nanotubes, graphite fibers and graphene;
[0028] 3) The active material layer does not contain detectable processing solvents, processing solvent residues, or processing solvent impurities.
[0029] In some embodiments, this application also provides a method for preparing an electrode sheet, comprising:
[0030] The active material, binder, conductive agent and conductive polymer fiber are mixed and hot-pressed to obtain the active material layer;
[0031] A current collector is provided, and the active material layer is combined with the current collector to obtain an electrode.
[0032] The preparation method does not include the use of processing solvents.
[0033] In some embodiments, in the active material layer, the active material has a mass percentage content of 90–98 wt%, the binder has a mass percentage content of 0.5–5 wt%, the conductive agent has a mass percentage content of 0.5–5 wt%, and the conductive polymer fiber has a mass percentage content of 0.05–1.65 wt%; and / or
[0034] The hot pressing temperature is 60–250°C; and / or
[0035] The thickness of the active material layer is 50–1000 μm.
[0036] In some embodiments, this application also provides a secondary battery, including the aforementioned electrode, or including the electrode prepared by the aforementioned preparation method.
[0037] In some embodiments, this application also provides an apparatus including the aforementioned secondary battery.
[0038] Beneficial Effects: Compared with the prior art, the electrode of this application includes a current collector and an active material layer disposed on the current collector. The active material layer includes conductive polymer fibers, the mass percentage of which is y wt%. The aspect ratio of the conductive polymer fibers is R, the conductivity is C ms / cm, and the tensile strength is σ MPa, satisfying: 0.5 < lg[(y × σ × R) / C] < 5.0. By adding conductive polymer fibers to the active material layer, this application can form a dense fiber network inside the electrode, increasing the degree of fiberization and providing good conductivity for the active material layer. This reduces the tortuosity and resistance of the electrode, which is more conducive to lithium-ion transport and electrolyte wetting, effectively improving the dynamic performance of the secondary battery.
[0039] It is understood that, compared with the prior art, the electrode preparation method, secondary battery and device provided in the embodiments of this application have all the technical features and beneficial effects of the above-mentioned electrode, which will not be repeated here. Detailed Implementation
[0040] The technical solutions in the embodiments of this application are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.
[0041] In the description of this application, "a plurality of" means two or more, unless otherwise expressly specified. Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, features defined as "first" or "second" may explicitly or implicitly include one or more features.
[0042] In the description of this application, the term "process" includes not only independent processes, but also processes that cannot be clearly distinguished from others, as long as the purpose of the process can be achieved. Furthermore, in this specification, the numerical range indicated by "~" represents a range where the values before and after the "~" are respectively the minimum and maximum values. Additionally, in this specification, the term "layer," when viewed in a plan view, includes not only the shape formed on the entire surface but also the shape formed on a portion of the surface.
[0043] The following disclosure provides many different implementations or examples for carrying out different structures of this application. To simplify the disclosure of this application, the components and arrangements of specific examples are described below. Of course, these are merely examples and are not intended to limit this application.
[0044] The applicant discovered that the traditional battery electrode manufacturing process is a wet process. First, a binder is dissolved in N-methylpyrrolidone to prepare a slurry. This slurry is then added to the positive and negative electrode active materials and conductive agent powders, and after thorough dispersion, it is coated. The advantage of this method is that the binder is dispersed relatively evenly. The disadvantage is that the coated electrode contains a large amount of solvent, requiring drying to remove it. This results in the wet coating process consuming a large amount of solvent and drying energy. Furthermore, during the drying process, the binder is prone to floating, leading to uneven dispersion and high electrode tortuosity. This causes electrode shedding and makes electrolyte wetting difficult, thus affecting the battery's kinetic performance. Therefore, thick electrodes prepared by the wet process, with increased areal density, are prone to becoming brittle and having smaller internal void structures. The lithium-ion transport path within the electrode becomes longer, leading to increased internal resistance and interfacial impedance, ultimately affecting the battery's kinetic performance.
[0045] Dry electrode fabrication differs from traditional wet slurry processes, offering inherent advantages in preparing thick electrodes. It can increase the compaction density and areal density of lithium-ion batteries, thereby effectively improving the energy density of the cell. Dry electrodes primarily utilize the inherent properties of fibrous binders to connect active materials and conductive agents into a fibrous network structure. This network structure enhances the uniformity of the mixture and provides excellent strength support, thus solving the problem of material shedding that easily occurs with wet slurries. Furthermore, dry electrodes do not require dissolution; the dry binder undergoes fibrosis through shear and friction forces, enabling the fabrication of electrodes with higher compaction densities and greater thicknesses. The larger porosity of the dry electrode membrane also facilitates lithium-ion transport, improving the cell's kinetic performance. Dry electrodes do not require complex equipment or solvent drying processes, significantly increasing battery fabrication efficiency.
[0046] Conventional dry electrode technology involves mixing active materials, conductive agents, and binders using kneading and mixing equipment. Due to the small particle size and large specific surface area of the conductive agents and binders, uneven dispersion and low degree of fibrosis are easily caused, resulting in low compaction density of the resulting support membrane. Furthermore, the degree of fibrosis of the binder is difficult to control; excessive fibrosis can also lead to high tortuosity of the support membrane, affecting the wettability of the electrolyte and thus impacting battery performance. In particular, the binder based on polytetrafluoroethylene (PTFE) relies on the fiberization of the PTFE binder to provide a certain membrane strength. However, due to different selection of positive and negative electrode materials and conductive agents, as well as different mixing processes, the degree of PTFE fiberization in the mixed powder can be directly affected. This may lead to the agglomeration of more PTFE particles, resulting in uneven fiberization. Insufficient fiberization leads to lower membrane compaction density and poorer tensile strength of the electrode. PTFE binder fiberization may also cause increased tortuosity of the electrode, affecting electrolyte wetting. Therefore, the performance of the resulting support membrane needs further optimization.
[0047] Therefore, based on the above problems, there is a need to provide an electrode, a preparation method, a secondary battery, and a device that improve the tensile strength of the self-supporting membrane and the porosity structure of the electrode by adding conductive polymer fibers, thereby improving electron transport performance, reducing the resistivity of the electrode, and reducing tortuosity.
[0048] This application provides an electrode sheet, including a current collector and an active material layer disposed on the current collector. The active material layer includes conductive polymer fibers, the mass percentage of which is y wt%; the aspect ratio of the conductive polymer fibers is R, the conductivity of which is Cms / cm, and the tensile strength of which is σMPa, satisfying: 0.5<lg[(y×σ×R) / C]<5.0.
[0049] Understandably, the addition of conductive polymer fibers can improve the tensile strength of the electrode, increase electronic conductivity, reduce electrode resistance, and decrease tortuosity. Specifically, by introducing conductive polymer fibers into the active material layer, the performance of the electrode is improved, avoiding the shortcomings of a single binder. Conductive polymer fibers can construct a more complete porous structure, which is beneficial for improving the internal porosity of the electrode, improving the electronic conductivity of the electrode, enabling the fabrication of thicker electrodes, and improving the wetting performance of the electrolyte and the kinetic performance of the battery.
[0050] Furthermore, to balance the overall performance of the electrode, the content, aspect ratio, conductivity, and tensile strength of the conductive polymer fiber should be rationally controlled. When the range of 0.5 < lg[(y × σ × R) / C] < 5.0 is met, the aspect ratio of the conductive polymer fiber can effectively improve the electronic conductivity. The larger the aspect ratio, the faster electrons migrate along the surface of the conductive polymer fiber, and the better the conductivity. The higher the tensile strength of the conductive polymer fiber, the higher the strength of the prepared electrode. The amount of conductive polymer fiber added determines the degree of fiberization in the entire electrode. The added conductive polymer fiber is used to form a dense fiber network, providing good conductivity for the electrode, reducing the tortuosity and resistance of the electrode, which is more conducive to lithium ion transport and electrolyte wetting, and can effectively improve the rate performance of the battery.
[0051] In some embodiments, the conductive polymer fiber may be in the shape of a round rod or a long rod.
[0052] In some embodiments, the value of lg[(y×σ×R) / C] can be any one of the following values or a range between any two values: 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9.
[0053] In some embodiments, the electrode further satisfies: 0.8 < lg[(y × σ × R) / C] < 3.5.
[0054] In some embodiments, the electrode further satisfies: 1.1 < lg[(y×σ×R) / C] < 1.4.
[0055] In some embodiments, the conductive polymer fiber is selected from at least one of conductive polyvinylidene fluoride fiber, conductive polytetrafluoroethylene fiber, conductive polyacrylonitrile fiber, conductive nylon fiber, conductive polyester fiber, and conductive polyetheretherketone fiber. A conductive polymer fiber is a fiber material with conductive properties, prepared by spinning a polymer or polymer composite with high conductivity. In this application, the conductive polymer fiber can be a commercially available conductive polymer fiber or a composite fiber prepared from a polymer and a conductive agent. In this application, the preparation of conductive polymer nanofibers is not limited and can be prepared by processes such as electrospinning, melt spinning, solution spinning, wet spinning, and dry spinning.
[0056] Furthermore, the preparation process of conductive polyvinylidene fluoride fiber is as follows: polyvinylidene fluoride, conductive agent and polar solvent are mixed to form a conductive solution, and then prepared by solution spinning.
[0057] Furthermore, the preparation process of conductive polytetrafluoroethylene fiber is as follows: polytetrafluoroethylene, conductive agent and additives are mixed and compacted to obtain a film, and the film is then stretched and heat-set to obtain the final product.
[0058] In some embodiments, the aspect ratio R of the conductive polymer fiber satisfies: 200 ≤ R ≤ 1000. For example, R can be any one value or a range between any two values from 200, 300, 400, 500, 600, 700, 800, 900, and 1000. Having an aspect ratio within the above range is beneficial for improving the electronic conductivity of the conductive polymer fiber.
[0059] In some embodiments, the conductivity C ms / cm of the conductive polymer fiber satisfies: 1 ≤ C ≤ 30000. For example, C can be any one value or a range between any two values from 1, 10, 20, 50, 80, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 2000, 5000, 8000, 10000, 15000, 20000, 25000, and 30000. The preferred range for the conductivity C of the conductive polymer fiber is 30-1000 ms / cm, with conductive polyacrylonitrile fiber exhibiting the highest conductivity, approaching that of a conductor. Within the aforementioned conductivity range, the conductive polymer fiber achieves faster electron transport speeds, lower resistance, more uniform conductivity, and better stability.
[0060] In some embodiments, the tensile strength σ MPa of the conductive polymer fiber satisfies: 1 ≤ σ ≤ 100. For example, σ can be any one value or a range between any two values from 1, 5, 8, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100. Having the tensile strength of the conductive polymer fiber within the above range is beneficial for improving the overall strength of the electrode, thereby ensuring battery performance.
[0061] In some embodiments, the mass percentage y wt% of the conductive polymer fiber satisfies: 0.05 ≤ y ≤ 1.65. For example, y can be any one value or a range between any two values from 0.05, 0.08, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65. When the percentage of conductive polymer fiber is within the above range, it can form a dense fiber network together with the virgin fibrillation produced by binders, etc., providing good conductivity for the electrode and further facilitating lithium-ion transport and electrolyte wetting.
[0062] In some embodiments, the mass percentage y wt% of the conductive polymer fiber satisfies: 0.3 ≤ y ≤ 0.8.
[0063] In some embodiments, the diameter of the conductive polymer fiber is 0.01–1 μm, preferably 0.1–1 μm. For example, the diameter of the conductive polymer fiber can be any one or a range between any two of the following: 0.01 μm, 0.02 μm, 0.05 μm, 0.06 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, and 1.0 μm.
[0064] In some embodiments, the length of the conductive polymer fiber is 10–1000 μm, preferably 10–500 μm. For example, the length of the conductive polymer fiber can be any one value or a range between any two values selected from 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, 600 μm, 650 μm, 700 μm, 750 μm, 800 μm, 850 μm, 900 μm, 950 μm, and 1000 μm.
[0065] In some embodiments, the active material layer further includes an active material and a binder, wherein the binder comprises b wt% by mass in the active material layer; and the specific surface area of the active material is S g / cm³. 2 The compaction density of the electrode is PD g / cm³. 3 The tortuosity of the electrode is T, which satisfies: 1.4≤(S×T×b) / (PD×y)≤9.
[0066] It is understandable that the specific surface area of the active material is related to the compaction density and tortuosity of the electrode. A larger specific surface area of the active material is more conducive to improving the compaction density of the electrode. Furthermore, the specific surface area of the active material, the mass percentage of the binder, and the mass percentage of the conductive polymer fibers jointly determine the internal network structure of the electrode. Specifically, the virgin fibrous material formed after the binder undergoes fibrosis, along with the conductive polymer fibers, are distributed within the electrode to adsorb particles such as active materials and conductive agents, forming a more extensive long-range and short-range interactive conductive network. This is more conducive to the transport of electrons and ions, reducing the electrode's resistance and tortuosity, thereby improving the battery's rate performance. Under the condition of 1.4 ≤ (S×T×b) / (PD×y) ≤ 9, the electrode exhibits better electrolyte wettability, lower electrode resistivity, and stronger tensile strength, which can reduce the amount of binder used and improve the battery's kinetic performance.
[0067] In some embodiments, the range of (S×T×b) / (PD×y) can be any one of 1.4, 1.5, 1.8, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0 or a range between any two values.
[0068] In some embodiments, the electrode further satisfies: 1.5≤(S×T×b) / (PD×y)≤2.
[0069] In some embodiments, the specific surface area of the active material is S g / cm³ 2 The following condition must be met: 0.3 ≤ S ≤ 1.5. For example, S can be any one value or a range between any two values from 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, and 1.5. Having a specific surface area of the active material within the above range is beneficial for increasing the compaction density of the electrode.
[0070] In some embodiments, the mass percentage of binder, b wt%, satisfies the condition: 0.5 ≤ b ≤ 5. For example, b can be any one or a range between any two values from 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0. A binder mass percentage within the above range is beneficial for forming a longer and denser network structure within the electrode, improving electron and ion transport.
[0071] In some embodiments, the mass percentage of active material is 90 to 98 wt% based on the total mass of the active material layer. For example, the mass percentage of active material is any one or a range between any two of the following values: 90 wt%, 91 wt%, 92 wt%, 93 wt%, 94 wt%, 95 wt%, 96 wt%, 97 wt%, and 98 wt%.
[0072] In some embodiments, the conductive polymer fibers account for 0.1 to 33 wt% of the total binder. For example, it can be any one or a range between any two values from 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 1.0 wt%, 1.2 wt%, 1.5 wt%, 2.0 wt%, 2.5 wt%, 3.0 wt%, 5.0 wt%, 6.0 wt%, 7.0 wt%, 8.0 wt%, 9.0 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 31 wt%, 32 wt%, and 33 wt%.
[0073] In some embodiments, the compaction density PD of the electrode is [missing value] g / cm³. 3 The following condition must be met: 3.2 ≤ PD ≤ 4. For example, PD can be any one or any two values from 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, and 4.0. The compaction density of the electrode reflects the tightness between components such as the active material, conductive agent, binder, and conductive polymer fibers. Meeting the above-mentioned range is beneficial for improving the electrode's conductivity, charge transport rate, and reactivity, thereby improving battery performance.
[0074] In some embodiments, the tortuosity T of the electrode satisfies: 1.5 ≤ T ≤ 3. For example, T can be any one of 1.5, 1.8, 2.0, 2.2, 2.5, 2.8, 3.0, or a range between any two values. The tortuosity of the electrode reflects its flexibility and deformability. Meeting the above range allows for optimization of the battery's structure and performance, improving its cycle life, energy storage capacity, and stability.
[0075] In some embodiments, the active material layer does not contain detectable processing solvents, processing solvent residues, or processing solvent impurities. In this application, processing solvent refers to the processing solvent used in the wet fabrication of the electrode sheet. These processing solvents include, but are not limited to, water, pyrrolidone, acetate, ketones, alcohols, diols, toluene, and xylene.
[0076] In some embodiments, the electrode is a positive electrode, and the active material is a positive active material selected from LiNi as shown in the formula. m Co n A (1-m-n)The lithium transition metal oxide represented by O2, wherein A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium and tungsten, and 0.5≤m≤1, 0≤n≤0.5.
[0077] In some embodiments, the electrode is a positive electrode, and the active material is a positive active material selected from LiNi as shown in the formula. m Co n A (1-m-n) The lithium transition metal oxide represented by O2, wherein A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium and tungsten, and 0.7≤m≤1, 0≤n≤0.3.
[0078] In some embodiments, the positive electrode active material is selected from LiNi as shown in the example. m Co n Mn (1-m-n) The lithium transition metal oxide shown in O2 has a 0.5 ≤ m ≤ 1 and a 0 ≤ n ≤ 0.5.
[0079] In some embodiments, the positive electrode active material is selected from LiNi as shown in the example. m Co n Mn (1-m-n) The lithium transition metal oxide represented by O2 has a density of 0.7 ≤ m ≤ 1 and a density of 0 ≤ n ≤ 0.3. In some embodiments, the positive electrode active material is selected from LiNi. 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.9 Co 0.05 Mn 0.05 Any one or more of O2.
[0080] It is understandable that the positive electrode active material uses a high-nickel ternary system material, which can be used to store and release charge, provide battery potential and determine battery capacity. In addition, the conductivity, reaction rate, cycle stability and electrolyte compatibility of the positive electrode active material will affect the battery's power output, cycle life and safety. Using the above-mentioned positive electrode active material can ensure the battery's cycle life, power output and safety performance.
[0081] In some embodiments, the binder is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, polyethylene glycol, carboxymethyl cellulose, and polyacrylate. During the mixing process, the binder is subjected to external force to fibrousize and form virgin fibers, which can together with the conductive polymer fibers added in this embodiment to form a network structure for bonding electrode materials, maintaining electrode structural stability, promoting charge conduction, and regulating electrode pore structure.
[0082] In some embodiments, the active material layer further includes a conductive agent, the conductive agent having a mass percentage content of 0.5 to 5 wt% in the active material layer; for example, the mass percentage content of the conductive agent can be any one or a range between any two of the following values: 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1.0 wt%, 1.5 wt%, 2.0 wt%, 2.5 wt%, 3.0 wt%, 3.5 wt%, 4.0 wt%, 4.5 wt%, and 5.0 wt%.
[0083] In some embodiments, the conductive agent is selected from at least one of conductive carbon black, Ketjen black, carbon nanotubes, carbon fibers, and graphene. It is understood that the addition of the conductive agent can provide an electronic conduction path, improve the conductivity of the electrode material, increase the contact area of the electrode material, improve the dispersibility of the electrode material, and prevent the electrode material from peeling, breaking, or deforming.
[0084] In some embodiments, this application also provides a method for preparing an electrode sheet, comprising:
[0085] The active material, binder, conductive agent and conductive polymer fiber are mixed and hot-pressed to obtain the active material layer;
[0086] A current collector is provided, and the active material layer is combined with the current collector to obtain an electrode.
[0087] The preparation method does not include the use of processing solvents.
[0088] It is understandable that in the above preparation method, the addition of conductive polymer fibers increases the compaction density of the electrode, reduces the tortuosity of the electrode, improves the electronic conductivity of the electrode, and further improves the wetting performance of the electrolyte and enhances the kinetic performance of the battery.
[0089] In some embodiments, the step of mixing the active material, binder, conductive agent, and conductive polymer fiber, and hot-pressing to obtain the active material layer further includes:
[0090] Active materials, binders, conductive agents, and conductive polymer fibers are mechanically mixed to obtain a premix. This premix is then pretreated through processes such as extrusion and high-speed dispersion using mechanical equipment, resulting in the initial fiberization of the binder and the formation of a pre-fibered flocculent mixture. For example, the initial mixture can be formed using high-speed shearing of a dispersing disc. The initial mixing equipment is a high-speed rotary-rotating mixer, where the dispersing disc speed is controlled at 2000–10000 rpm, preferably 4000–8000 rpm, and the rotary disc speed is 20–60 rpm, preferably 30–50 rpm. The mixture is first premixed at 3000 rpm for 2 minutes, then mixed at 5600 rpm for 5 minutes. After the material cools to room temperature, a uniformly mixed material with a high degree of fiberization is obtained. The pre-fiberized product is then hot-pressed, such as on a roller press or open mill. The shearing force of the roller press and the friction between the materials further fiberize the binder. During this process, the random arrangement and distribution of conductive polymer nanofibers are intensified, forming a layer of active material with high strength.
[0091] In some embodiments, the step of providing a current collector and combining the active material layer with the current collector to obtain an electrode further includes:
[0092] The active material layer and the current collector are rolled together to form a complete electrode sheet; wherein, the active material layer can be a positive active material layer or a negative active material layer; the positive active material layer is combined with an aluminum current collector, and the negative active material layer is combined with a copper current collector; the current collector can be a foil or a current collector coated with a conductive layer.
[0093] In some embodiments, based on the total mass of the active material layer, the mass percentage of the active material is 90–98 wt%, the mass percentage of the binder is 0.5–5 wt%, the mass percentage of the conductive agent is 0.5–5 wt%, and the mass percentage of the conductive polymer fiber is 0.05–1.65 wt%.
[0094] In some embodiments, the hot-pressing temperature is 60–250°C; for example, it can be any one or a range between any two of the following values: 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, and 250°C.
[0095] In some embodiments, the thickness of the active material layer is 50–1000 μm, preferably 50–200 μm; for example, the thickness of the active material layer can be any one or any range between any two of the following values: 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, and 1000 μm.
[0096] In some embodiments, this application also provides a secondary battery, including the aforementioned electrode sheets, wherein the electrode sheets include a positive electrode sheet; the secondary battery further includes a negative electrode sheet, a separator membrane disposed between the positive electrode sheet and the negative electrode sheet, and an electrolyte. The following provides further supplementary descriptions of the positive electrode sheet, negative electrode sheet, separator membrane, and electrolyte in the secondary battery.
[0097] The positive electrode includes a positive current collector and a positive active material layer disposed on the positive current collector.
[0098] In some embodiments, the positive electrode active material layer can be one or more layers. Each layer in a multilayer positive electrode active material can contain the same or different positive electrode active materials. The positive electrode active material is any substance capable of reversibly inserting and deintercalating metal ions such as lithium ions.
[0099] In some embodiments, the positive electrode active material contains doping elements and / or coating elements. There are no special requirements for the doping elements and / or coating elements, as long as they can make the positive electrode active material more stable.
[0100] In addition, the positive electrode active material layer also includes a positive electrode conductive agent, a positive electrode binder, and conductive polymer fibers. There are no restrictions on the types of positive electrode conductive agents and binders; any known conductive agent can be used. The positive electrode conductive agent and binder can be used alone or in any combination. The conductive polymer fibers are selected from at least one of conductive polyvinylidene fluoride fibers, conductive polytetrafluoroethylene fibers, conductive polyacrylonitrile fibers, conductive nylon fibers, conductive polyester fibers, and conductive polyetheretherketone fibers.
[0101] In some embodiments, the type of positive electrode current collector is not particularly limited, and it can be any known material suitable for use as a positive electrode current collector. Examples of positive electrode current collectors include, but are not limited to, metallic materials such as aluminum, stainless steel, nickel plating, titanium, and tantalum; carbon materials such as carbon cloth and carbon paper; and composite materials formed by polymers and metal layers. In some embodiments, the positive electrode current collector is a metallic material. In some embodiments, the positive electrode current collector is aluminum. The form of the positive electrode current collector is not particularly limited. When the positive electrode current collector is a metallic material, its form may include, but is not limited to, metal foil, metal cylinder, metal strip, metal plate, metal foil, metal mesh, stamped metal, foamed metal, etc. When the positive electrode current collector is a carbon material, its form may include, but is not limited to, carbon plate, carbon film, carbon cylinder, etc.
[0102] In some embodiments, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one surface of the negative current collector. The negative active material layer contains a negative active material selected from at least one of natural graphite, artificial graphite, hard carbon, soft carbon, mesophase carbon microspheres, silicon oxides, and silicon carbide compounds. It is understood that the negative active material corresponds to the positive active material and is also used to store and release charge, provide battery potential, and determine battery capacity. Using the aforementioned negative active material can ensure the battery's cycle life, power output, and safety performance.
[0103] In some embodiments, a separator is typically provided between the positive and negative electrodes to prevent short circuits. The type of separator is not particularly limited and can be selected according to actual needs. The separator can be a polypropylene film, polyethylene film, polyvinylidene fluoride film, spandex film, aramid film, or a multilayer composite film modified with a coating.
[0104] In some embodiments, the preparation of a secondary battery includes: stacking a positive electrode, a separator, and a negative electrode in sequence, with the separator positioned between the positive and negative electrodes to provide isolation, then winding it into a bare battery, inserting it into a battery casing, baking it at 65–95°C to remove water, injecting electrolyte, sealing it, and then performing processes such as standing, hot and cold pressing, formation, and capacity testing to obtain a secondary battery.
[0105] In some embodiments, the secondary battery may include an outer packaging, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft pack, such as a pouch-type soft pack, and the material of the soft pack may be plastic, such as one or more of polypropylene, polybutylene terephthalate, polybutylene succinate, etc.
[0106] In some embodiments, the shape of the secondary battery is not particularly limited, and it can be cylindrical, square or other arbitrary shapes.
[0107] Device
[0108] In some embodiments, this application provides an apparatus including the aforementioned secondary battery. The apparatus can be an application device such as a vehicle, mobile phone, portable device, laptop computer, ship, spacecraft, electric toy, and power tool. Vehicles can be new energy vehicles, including pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles; spacecraft include airplanes, rockets, space shuttles, and spacecraft; electric toys include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys; power tools include metal cutting power tools, grinding power tools, assembly power tools, and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators, and electric planers. This application does not impose any special limitations on the aforementioned apparatus.
[0109] This application has undergone numerous experiments, and some of the test results are presented below for reference to further describe the invention in detail. Specific embodiments are described in detail below. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application.
[0110] The conductive polyvinylidene fluoride (PVDF) fibers used in the embodiments and comparative examples of this application were prepared by the following method: (1) Polyvinylidene fluoride powder and conductive carbon black particles were dry-mixed evenly. This step can be carried out using a mechanical stirrer. The molecular weight of polyvinylidene fluoride is 300,000 to 1,000,000, and the primary particles of conductive carbon black are about 40 nm; (2) Polar solvents, such as N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), and N-methylpyrrolidone (NMP), were added to the mixed powder to prepare a mixed conductive solution with a mass concentration of 5% to 20%; 3) The above-mentioned mixed conductive solution is used as the spinning solution and drawn into a 20mL syringe. The syringe is fixed to the injection pump of the spinning machine and fitted with a 20G (1 / 2 inch, flat-mouth) stainless steel needle. The needle is connected to the positive terminal of the high-voltage power supply, and the receiving roller is connected to the negative terminal of the high-voltage power supply. The receiving substrate is attached to the roller. The injection pump is set to 20mL, the liquid supply rate is 2mL / h, the roller speed is 300 rpm, the slide stroke is 20cm, the spinning distance is 15cm, the spinning voltage is positive 15kV and negative 5kV, the temperature is 35℃, the humidity is 40%, and the timer is 120min. Finally, the equipment door is closed and the exhaust is turned on. Conductive polyvinylidene fluoride fiber can be obtained on the electrospinning receiving substrate.
[0111] The diameter of the conductive polyvinylidene fluoride (PVDF) fibers is controlled by adjusting the mass concentration of the spinning solution. Furthermore, it can be understood that increasing the PVDF concentration in the spinning solution increases the diameter of the resulting conductive PVDF fibers, while decreasing the PVDF concentration decreases the diameter. In this embodiment, the concentration of the spinning solution is selected to be 5%-20%, allowing for control of the PVDF fiber diameter within this range. Additionally, the length of the conductive PVDF fibers can be adjusted by regulating the voltage in the spinning process and reducing the distance between the needle and the collector, thereby adjusting the fiber length to meet experimental requirements.
[0112] The conductive polytetrafluoroethylene fiber (PTFE) used was prepared as follows: polytetrafluoroethylene powder with a number average molecular weight of more than 1 million was taken, a lubricating oil with a low relative molecular mass was selected as an additive, and nano-sized conductive carbon black was used as a conductive additive. The specific method is as follows: (1) First, the lubricant, nano-sized conductive carbon black and polytetrafluoroethylene powder were mixed and stirred at room temperature in a mass ratio of 15:5:85, and then mixed in a V-type mixer for 24 hours to fully wet and disperse the powder evenly to obtain a viscous mixture; (2) The mixture was loaded into a cylindrical closed tubular mold for pre-compression, and the compaction density reached 1800 kg / m³. 3 Then the raw material is transferred to the extruder and extruded at a certain speed. The extruded product is dried in the oven at a temperature of 150°C for 12 hours to allow the lubricating oil to evaporate. (3) The film is pressed into a thin film at room temperature and a pressure of 40 MPa. The film is stretched to 5-6 times at 270°C to obtain a wound filament. The wound filament is further stretched and heat-set at 380°C to obtain conductive polytetrafluoroethylene fiber.
[0113] In the extrusion process of the aforementioned viscous mixture, changes in extrusion pressure have a significant impact on the final fiber formation. Higher pressure results in finer fibers with smaller diameters. In this embodiment, the fiber diameter is adjusted by controlling the extrusion pressure. Furthermore, the obtained fibers are processed into fibers of different lengths according to the required lengths using a fiber cutting machine.
[0114] The conductive polyacrylonitrile (PAN) fibers, conductive nylon (PA) fibers, and other materials and reagents used were all commercially available.
[0115] Example 1
[0116] LiNi 0.9 Co 0.05 Mn 0.05O2, conductive carbon black Super P, polytetrafluoroethylene (PTFE), and conductive PTFE fiber were mechanically mixed at a mass ratio of 96.5:1.7:1.5:0.3. The dispersion disc rotated at 3000 rpm for 10 minutes. Then, a second mechanical mixing was performed using a high-speed mixer. The dispersion disc was rotated at 2000 rpm for 5 minutes, and then the rotation speed was increased to 5000 rpm for 10 minutes to obtain a highly fibrous powder. The powder was then hot-pressed at 80°C. After two rounds of rolling, a 150 μm thick positive electrode active material layer was formed. The positive electrode active material layer was then rolled and laminated with aluminum foil to form a complete positive electrode sheet.
[0117] Graphite, nano-silicon powder, conductive carbon black Super P, CMC (sodium carboxymethyl cellulose), and SBR (styrene-butadiene rubber) binder were mixed in a ratio of 88.32:7.68:1.0:1.5:1.5. H2O was added and the mixture was kneaded and stirred at a linear speed of 13 m / s. The solid content of the kneaded mixture was controlled at 70%. Water was then added, and high-speed stirring continued until the final slurry viscosity was adjusted to 4500 mPa·s, with a solid content of approximately 54%. The slurry was then coated onto a 6 μm thick copper foil to form a complete negative electrode sheet. The areal density of the negative electrode sheet was 11 mg / cm³. 2 The compaction density of the negative electrode sheet is 1.6 g / cm³. 3 .
[0118] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes. After winding, hot pressing and shaping, and welding of the tabs, a bare battery is obtained. The bare battery is placed in an outer aluminum-plastic film and baked in an oven at 85±10℃ for 24 hours. The electrolyte is injected into the dried battery, and the battery is allowed to stand, form, and be tested for capacity to complete the preparation of the secondary battery.
[0119] Example 2
[0120] The specific preparation process is the same as in Example 1, except that: LiNi 0.9 Co 0.05 Mn 0.05 The mass ratio of O2, conductive carbon black Super P, polytetrafluoroethylene, and conductive polytetrafluoroethylene fiber is 95.5:2.0:2.0:0.5.
[0121] Example 3
[0122] The specific preparation process is the same as in Example 1, except that: LiNi 0.9 Co 0.05 Mn 0.05The mass ratio of O2, conductive carbon black Super P, polytetrafluoroethylene, and conductive polytetrafluoroethylene fiber is 94.5:3.9:1.3:0.3.
[0123] Example 4
[0124] The specific preparation process is the same as in Example 1, except that: LiNi 0.9 Co 0.05 Mn 0.05 The mass ratio of O2, conductive carbon black Super P, polytetrafluoroethylene, and conductive polytetrafluoroethylene fiber is 95.5:1.9:1.8:0.8.
[0125] Example 5
[0126] The specific preparation process is the same as in Example 1, except that LiNi 0.9 Co 0.05 Mn 0.05 The mass ratio of O2, conductive carbon black Super P, polytetrafluoroethylene, and conductive polytetrafluoroethylene fiber is 93.5:3.1:3.0:0.4.
[0127] Example 6
[0128] The specific preparation process is the same as in Example 1, except that LiNi 0.9 Co 0.05 Mn 0.05 The mass ratio of O2, conductive carbon black Super P, polytetrafluoroethylene, and conductive polytetrafluoroethylene fiber is 94.5:3.0:2.0:0.5.
[0129] Example 7
[0130] The specific preparation process is the same as in Example 1, except that:
[0131] In the preparation of the positive electrode sheet, the mixed powder is LiNi 0.5 Co 0.2 Mn 0.3 O2, conductive carbon black Super P, polyvinylidene fluoride, and conductive polytetrafluoroethylene fiber are mixed in a mass ratio of 96.5:2.9:0.5:0.1.
[0132] Example 8
[0133] The specific preparation process is the same as in Example 1, except that:
[0134] In the preparation of the positive electrode sheet, the mixed powder is LiNi 0.6 Co 0.2 Mn 0.2O2, carbon nanotubes, tetrafluoroethylene-hexafluoropropylene copolymer, and conductive polyvinylidene fluoride fiber were mixed in a mass ratio of 94.5:4.3:1.0:0.2.
[0135] Example 9
[0136] The specific preparation process is the same as in Example 1, except that:
[0137] In the preparation of the positive electrode sheet, the mixed powder is LiNi 0.8 Co 0.1 Mn 0.1 O2, Ketjen Black, carboxymethyl cellulose, and conductive nylon fiber were mixed in a mass ratio of 96.7:1.5:1.5:0.3.
[0138] Example 10
[0139] The specific preparation process is the same as in Example 1, except that:
[0140] In the preparation of the positive electrode sheet, the mixed powder is LiNi 0.9 Co 0.05 Mn 0.05 O2, conductive carbon black Super P, polytetrafluoroethylene, and conductive polyester fiber are mixed in a mass ratio of 96.0:1.5:2.0:0.5.
[0141] Example 11
[0142] The specific preparation process is the same as in Example 1, except that:
[0143] In the preparation of the positive electrode sheet, the mixed powder is LiNi 0.9 Co 0.05 Mn 0.05 O2, conductive carbon black Super P, polytetrafluoroethylene, and conductive polyacrylonitrile fiber are mixed in a mass ratio of 93.0:3.01:3.0:0.99.
[0144] Example 12
[0145] The specific preparation process is the same as in Example 1, except that:
[0146] In the preparation of the positive electrode sheet, the mixed powder is LiNi 0.9 Co 0.05 Mn 0.05 O2, conductive carbon black Super P, polytetrafluoroethylene, and conductive polyacrylonitrile fiber are mixed in a mass ratio of 92.0:2.5:5.0:0.5.
[0147] Examples 13-19
[0148] The specific preparation process is the same as in Example 1, except that the mass ratio of the mixed powder, the aspect ratio of the conductive polymer fiber, the conductivity of the conductive polymer fiber, and the tensile strength of the conductive polymer fiber are different from those in Example 1. See Table 1 for details.
[0149] Comparative Examples 1-8 are provided, wherein no conductive polymer fibers are added when preparing the positive electrode sheet in Comparative Examples 1-2; the positive electrode sheets of Comparative Examples 3-4 do not meet the range of 0.5 < lg[(y×σ×R) / C] < 5.0; and the positive electrode sheets of Comparative Examples 5-8 do not meet the ranges of 0.5 < lg[(y×σ×R) / C] < 5.0 and 1.4 ≤ (S×T×b) / (PD×y) ≤ 9.
[0150] The parameters of the positive electrode plates of Examples 1-19 and Comparative Examples 1-8 above, as well as the corresponding secondary battery test characterization performance data, are shown in Tables 1, 2 and 3.
[0151] It should be noted that the amount of binder and conductive polymer fiber added during preparation can be equivalent to their content in the corresponding active material layer.
[0152] The conductivity test method for conductive polymer fibers is as follows: A high-resistivity meter is used for testing. The ratio of the current flowing through the volume of the fiber assembly to the voltage difference generated is used to calculate the conductivity per unit cross-sectional area (cm²). 2 The resistance per unit length (cm) is the volume resistivity (Ω·cm), or the resistance per unit length (cm) and unit mass (g) is the mass resistivity (Ω·g / cm). 2 The surface resistivity is calculated by the ratio of the DC field strength passing through the surface of the fiber assembly to the surface current per unit width.
[0153] The tensile strength test method for conductive polymer fibers is as follows: The tensile strength is tested using the strip method. The entire width of the specimen is clamped within a specified clamp, and the tensile test is performed at a constant tensile rate until breakage. The breaking strength and elongation at break are recorded. The clamp width is 25 mm, the length is 40 mm, the tensile rate is 50 mm / min, and 5 points are tested for each group of specimens.
[0154] The test method for the compaction density of the electrode sheet is as follows: Take the rolled electrode sheet, cut off a section with a circular or square cutter, measure the thickness and weigh it. Wash away the positive electrode material with an acetone-alcohol mixture and blow dry. Weigh the remaining aluminum foil and measure its thickness. Divide the difference between the two weights by the area to calculate the areal density. Divide the areal density by the thickness difference to obtain the compaction density.
[0155] The tortuosity of the electrode is tested using a mercury porosimeter. The pressure applied in the low-pressure station (LP) is approximately 0.6 to 50 PSI, and in the high-pressure station (HP), the pressure is 20 to 60,000 PSI. A glass cone probe is used as the sample container, and pressure is applied to the sample. The sample container has a volume of 0.5 cm³ and a length of 3.8 cm. The minimum pore size at maximum pressure is 3.56 nm. The electrode is cut into small pieces or rolled into a roll and placed in the sample container. Since the current collector is also placed in the sample container, the volume of the coating needs to be calculated by subtracting the current collector thickness from the electrode thickness when calculating the pore structure characteristic parameters. After obtaining the porosity ∈ [value missing], the tortuosity T is estimated using the Bruggeman equation.
[0156] The method for testing the tensile strength of the electrode is as follows: the prepared dry electrode is molded in the mold shown below, and then placed in a tensile testing machine at a tensile speed of 100 mm / min. The stress-strain curve of the electrode is recorded to obtain the tensile strength of the electrode.
[0157] The test method for electrode peel strength is as follows: cut the electrode into strips of 2×10cm, test them by tensile testing machine at a tensile speed of 100mm / min, record the stable tensile force value, and obtain the peel strength of the electrode.
[0158] The method for testing electrode resistivity is as follows: The overall resistivity of the electrode is directly measured using the dual-plane controllable pressure disc electrode resistance method with the BER series multi-functional electrode resistivity meter, including the resistance of the positive electrode active material layer, the contact resistance between the positive electrode active material layer and the current collector, and the sum of the current collector resistance.
[0159] The battery cycle performance test process is as follows: The cycle performance test is carried out at 25℃. The battery is charged at 0.5C to 4.2V, then charged at constant voltage to 0.05C. After resting for 10 minutes, it is discharged at 0.5C constant current to 2.5V, and then rested for 10 minutes. The above steps are repeated for 500 cycles. The capacity retention rate after the 500th cycle at 25℃ is calculated according to the following formula: Discharge capacity after the 500th cycle / Discharge capacity of the first cycle × 100%.
[0160] Table 1
[0161]
[0162]
[0163] Table 2
[0164]
[0165]
[0166] Table 3
[0167]
[0168] As shown in Tables 1, 2, and 3, Examples 1-6 satisfy the range of 0.5 < lg[(y × σ × R) / C] < 5.0. Under these conditions, the 0.5C discharge specific capacity and capacity retention rate after 500 cycles of the secondary battery are both higher than those of Comparative Examples 1-2. This indicates that the addition of conductive polymer fibers can effectively improve electronic conductivity, form a dense fiber network inside the positive electrode, and increase the degree of fiberization in the positive electrode. By adding conductive polymer fibers, the performance of the secondary battery is further improved to meet the actual product requirements.
[0169] Furthermore, Examples 7-19 simultaneously satisfy the ranges of 0.5 < lg[(y×σ×R) / C] < 5.0 and 1.4 ≤ (S×T×b) / (PD×y) ≤ 9. Compared to Examples 1-6 and Comparative Examples 3-8, the batteries exhibit higher capacity retention and larger discharge specific capacity, demonstrating superior overall performance. This is because the conductive polymer fibers can also form a more complete porous network structure together with the virgin fibers formed by the binder, which is beneficial for increasing the porosity inside the positive electrode, improving the electronic conductivity of the electrode, providing good conductivity for the electrode, reducing the tortuosity and resistance of the electrode, and is more conducive to lithium ion transport and electrolyte wetting, as well as improving the kinetic performance of the secondary battery.
[0170] The above provides a detailed description of an electrode, preparation method, secondary battery, and device provided in the embodiments of this application. Specific examples have been used in this application to illustrate the principles and implementation methods of this application. The description of the above embodiments is only for the purpose of helping to understand the technical solutions and core ideas of this application. Those skilled in the art should understand that they can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features; and these modifications or substitutions do not change the essence of the corresponding technical solutions.
Claims
1. An electrode sheet, characterized in that: It includes a current collector and an active material layer disposed on the current collector, the active material layer comprising conductive polymer fibers, an active material, and a binder; The conductive polymer fiber has a mass percentage content of y wt% in the active material layer; the aspect ratio of the conductive polymer fiber is R; the conductivity of the conductive polymer fiber is C ms / cm; and the tensile strength of the conductive polymer fiber is σ MPa, satisfying: 0.5<lg[(y×σ×R) / C]<5.0; The binder has a mass percentage content of b wt% in the active material layer; the specific surface area of the active material is S g / cm³. 2 The compaction density of the electrode sheet is PD g / cm³. 3 The tortuosity of the electrode is T, which satisfies: 1.4≤(S×T×b) / (PD×y)≤9; The preparation method of the electrode does not include the use of processing solvents.
2. The electrode sheet according to claim 1, characterized in that: The conductive polymer fiber satisfies at least one of the following characteristics: 1) Selected from at least one of conductive polyvinylidene fluoride fiber, conductive polytetrafluoroethylene fiber, conductive polyacrylonitrile fiber, conductive nylon fiber, conductive polyester fiber and conductive polyetheretherketone fiber; 2)200≤R≤1000; 3)1≤C≤30000; 4) 1 ≤ σ ≤ 100; 5) Diameter is 0.01~1μm; 6) Length is 10~1000μm; 7)0.05≤y≤1.65。 3. The electrode sheet according to claim 1, characterized in that: The electrode satisfies at least one of the following characteristics: 1)0.3≤S≤1.5; 2)0.5≤b≤5; 3) The active material has a mass percentage content of 90~98 wt% in the active material layer; 4) The conductive polymer fiber accounts for 0.1~33 wt% of the total amount of the adhesive; 5) 3.2 ≤ PD ≤ 4; 6)1.5≤T≤3。 4. The electrode sheet according to claim 3, characterized in that: The electrode is a positive electrode, and the active material is a positive active material selected from LiNi as shown in the formula. m Co n A (1-m-n) The lithium transition metal oxide represented by O2, wherein A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium and tungsten, and 0.5≤m≤1, 0≤n≤0.
5.
5. The electrode sheet according to claim 1, characterized in that: The electrode satisfies at least one of the following characteristics: 1) The adhesive is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, polyethylene glycol, carboxymethyl cellulose and polyacrylate; 2) The active material layer further includes a conductive agent, the conductive agent having a mass percentage content of 0.5~5wt% in the active material layer; the conductive agent is selected from at least one of conductive carbon black, Ketjen black, carbon nanotubes, carbon fibers and graphene; 3) The active material layer does not contain detectable processing solvents, processing solvent residues, or processing solvent impurities.
6. A method for preparing an electrode sheet, characterized in that, The method for preparing an electrode sheet as described in any one of claims 1-5 comprises: The active material, binder, conductive agent and conductive polymer fiber are mixed and hot-pressed to obtain the active material layer; A current collector is provided, and the active material layer is combined with the current collector to obtain an electrode. The preparation method does not include the use of processing solvents.
7. The preparation method according to claim 6, characterized in that, In the active material layer, the active material has a mass percentage of 90-98 wt%, the binder has a mass percentage of 0.5-5 wt%, the conductive agent has a mass percentage of 0.5-5 wt%, and the conductive polymer fiber has a mass percentage of 0.05-1.65 wt%; and / or, The hot pressing temperature is 60~250℃; and / or, The thickness of the active material layer is 50~1000 μm.
8. A secondary battery, characterized in that, The electrode includes any one of claims 1-5, or an electrode prepared by the method of claim 6 or 7.
9. An apparatus, characterized in that, Includes the secondary battery as described in claim 8.
Citation Information
Patent Citations
Pole piece, manufacturing method thereof and battery
CN116230868A
Electrode plate, preparation method thereof and solid-state battery
CN116779758A